2005
DOI: 10.1002/anie.200500026
|View full text |Cite
|
Sign up to set email alerts
|

Strong Means Slow: Dynamic Contributions to the Bulk Mechanical Properties of Supramolecular Networks

Abstract: The desire to control rationally, through small-molecule synthesis, the properties of bulk materials has led to supramolecular approaches to, for example, polymers, [1,2] strong and weak organogels, [3] amphiphilic assemblies, [4] and liquid crystals.[5] In these materials, specific and well-defined interactions between molecules contribute to bulk material properties on two levels: structure and dynamics. Although the dynamic nature of the defining interactions is often the attribute that distinguishes supram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
183
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(195 citation statements)
references
References 34 publications
11
183
1
Order By: Relevance
“…Presumably as the distance between two stickers along the chain is decreased, the relaxation of stress will require their concurrent unbinding. As a result, increasing the local concentration of UPy's leads to a correlation of their dynamics (also reflected in the flow activation energy, Figure 11), and as previously demonstrated, 27 it is the dynamics of unbinding and binding that dominate the macroscopic response.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Presumably as the distance between two stickers along the chain is decreased, the relaxation of stress will require their concurrent unbinding. As a result, increasing the local concentration of UPy's leads to a correlation of their dynamics (also reflected in the flow activation energy, Figure 11), and as previously demonstrated, 27 it is the dynamics of unbinding and binding that dominate the macroscopic response.…”
Section: Resultssupporting
confidence: 70%
“…In an early series of papers, Stadler and Freitas 11,[22][23][24] studied the rheological behavior of polybutadienes lightly modified with double-hydrogen-bonding phenylurazole groups, finding that even with light substitution along the backbone the storage modulus plateau was broadened and shifted to lower frequencies (although the overall network properties were primarily dictated by the highly entangled polymer backbone and the crystallization of the phenyl urazole side chains). More recently, reversible networks based on metal-ligand coordination have been synthesized and the macroscopic material properties directly related to the coordination dynamics; [25][26][27][28] in this case it was found that formation of a strong network required not just a high association constant but also slow dynamics of the reversible bond. Additionally, supramolecular gels based on hydrogen bonding in ionic liquids have been demonstrated and their rheological properties related to the strength and number of hydrogen bonds as well as stoichiometry of donor and acceptor units.…”
Section: Introductionmentioning
confidence: 99%
“…a) Schematic illustration of the phase diagram of polytetrafl uoroethylene (PTFE). Molecular packing and chain conformations of phase I, II, III, and IV are the disordered pseudohexagonal 15 7 helix, the triclinic 13 6 helix, the orthorhombic planar zigzag and the hexagonal 15 7 helix, respectively. The fi gure is redrawn from a previously published one.…”
Section: Resultsmentioning
confidence: 99%
“…Note that this work shows how dynamics and mechanism of metal-ligand exchange reactions are not only a qualitative but also a quantitative representation of the viscoelastic properties of bulk materials [78]. Although thermodynamics are a primary design consideration in supramolecular chemistry, the dynamics of the interactions are particularly important under nonequilibrium conditions, such as those imposed under mechanical stress [76,77,79]. Recently, Craig and coworkers used single-molecule force spectroscopy to study the mechanical activation of the ligand substitution reaction.…”
Section: Metallo-supramolecular Polymersmentioning
confidence: 99%
“…Steric effects in the spectator ligands of the complex, therefore, profoundly affect the rate of ligand exchange while having little effect on the stability of the complex. Pincer motifs have proven to be attractive in this regard due to the ease of steric manipulation of the spectator ligands and the added advantage of increased stability relative to the moderate stability of aryl Pd(II) complexes [76,77]. Using this approach, the authors studied supramolecular networks with a continuous 3D topology based on polypyridine and a ditopic pincer ligand (crosslinker) in DMSO.…”
Section: Metallo-supramolecular Polymersmentioning
confidence: 99%